3c+4=12+10.

Simple and best practice solution for 3c+4=12+10. equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3c+4=12+10. equation:



3c+4=12+10.
We move all terms to the left:
3c+4-(12+10.)=0
We add all the numbers together, and all the variables
3c+4-22=0
We add all the numbers together, and all the variables
3c-18=0
We move all terms containing c to the left, all other terms to the right
3c=18
c=18/3
c=6

See similar equations:

| x+2=-2x+11 | | (3-x)/(1-2x)=5 | | 1/6(2x+2)=1/3 | | 6^m+3=36 | | 3^3r+1=81 | | (x-12)^2=27 | | 10^4=(x^2+1) | | 2^-x-2=2^6 | | X+(0.06xX)=5 | | 5^-2m=5^3m | | 3(v+7)÷-3=7(v-1)÷-9 | | x^2+13x-7=15 | | x/4=6/10 | | 6y=3×,y=1/2× | | 3^-3n=9 | | t^2-t-3/2=0 | | 6x-52=4x+46 | | 23+4m=÷2 | | 2.7(n+7.8)+6.5=9n-4 | | p2-33p+16=0 | | n+(n+40)+(n-30)=150 | | 2m/5+7/10=9/2 | | 6(y+7.7)-8y=-9 | | x*x*x+2x=26 | | 2x+1=7,x= | | -2x+7x=x | | 9(c+9.6)+6=5.2c+1.5 | | 9x-5(2x-9)=2(x-1)+9 | | 2(y+7)=5y-1 | | (3x)(-5x)=-2x | | 6x+(2x*2(2x*2-1)+(3x*2-1+2x)-2x+1)+2x-1=3 | | 0=4.6(t+9.5) |

Equations solver categories